Waterborne transmission of protozoan parasites: a review of worldwide outbreaks - an update 2017-2022 - Pavlina Bourli; Aida Vafae Eslahi; Ourania Tzoraki; Panagiotis Karanis (IWA Publishing, 2023)
The current study presents a comprehensive review of worldwide waterborne parasitic protozoan outbreaks reported between 2017 and 2022. In total, 416 outbreaks were attributed to the waterborne transmission of parasitic protozoa. Cryptosporidium accounted for 77.4% (322) of outbreaks, while Giardia was identified as the etiological agent in 17.1% (71). Toxoplasma gondii and Naegleria fowleri were the primary causes in 1.4% (6) and 1% (4) of outbreaks, respectively. Blastocystis hominis, Cyclospora cayetanensis, and Dientamoeba fragilis were independently identified in 0.72% (3) of outbreaks. Moreover, Acanthamoeba spp., Entamoeba histolytica, Vittaforma corneae, and Enterocytozoon bieneusi were independently the causal agents in 0.24% (1) of the total outbreaks. The majority of the outbreaks (195, 47%) were reported in North America. The suspected sources for 313 (75.2%) waterborne parasitic outbreaks were recreational water and/or swimming pools, accounting for 92% of the total Cryptosporidium outbreaks. Furthermore, 25.3% of the outbreaks caused by Giardia were associated with recreational water and/or swimming pools. Developing countries are most likely to be impacted by such outbreaks due to the lack of reliable monitoring strategies and water treatment processes. There is still a need for international surveillance and reporting systems concerning both waterborne diseases and water contamination with parasitic protozoa. HIGHLIGHTS 416 waterborne protozoan outbreaks were identified between 2017 and 2022, globally.; Cryptosporidium was the most common etiological agent.; The majority of the outbreaks were reported in North America.; The number of reported waterborne outbreaks in developed countries were higher than developing countries.; Recreational water and/or swimming pools were the suspected source of infection in most of the reports.;